2010
DOI: 10.1039/c0ob00102c
|View full text |Cite
|
Sign up to set email alerts
|

Manganese catalyzed cis-dihydroxylation of electron deficient alkenes with H2O2

Abstract: A practical method for the multigram scale selective cis-dihydroxylation of electron deficient alkenes such as diethyl fumarate and N-alkyl and N-aryl-maleimides using H(2)O(2) is described. High turnovers (>1000) can be achieved with this efficient manganese based catalyst system, prepared in situ from a manganese salt, pyridine-2-carboxylic acid, a ketone and a base, under ambient conditions. Under optimized conditions, for diethyl fumarate at least 1000 turnovers could be achieved with only 1.5 equiv. of H(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
50
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 31 publications
4
50
0
Order By: Relevance
“…Effect of Acetic Acid on the Catalytic Oxidation of Alkenes. Previously, we demonstrated that the rate of reaction was dramatically reduced in the presence of acetic acid when the reaction was performed in acetone, albeit with relatively little effect on the overall conversion after 24 h. 29 The confirmation that acetic acid forms by decomposition of butanedione in the present system raises a question as to its effect on the conversion and reaction rate. The formation of acetic acid could potentially inhibit the catalytic system in one or more ways, including (i) the loss of butanedione results in reduced activity, since this is required for catalysis; (ii) the acetic acid affects the equilibrium between hydrogen peroxide/ butanedione and 3-hydroperoxy-3-hydroxybutan-2-one through reducing the effective nucleophilicity of H 2 O 2 ; and (iii) destabilizing a putative Mn(II)/PCA complex.…”
Section: ■ Results and Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Effect of Acetic Acid on the Catalytic Oxidation of Alkenes. Previously, we demonstrated that the rate of reaction was dramatically reduced in the presence of acetic acid when the reaction was performed in acetone, albeit with relatively little effect on the overall conversion after 24 h. 29 The confirmation that acetic acid forms by decomposition of butanedione in the present system raises a question as to its effect on the conversion and reaction rate. The formation of acetic acid could potentially inhibit the catalytic system in one or more ways, including (i) the loss of butanedione results in reduced activity, since this is required for catalysis; (ii) the acetic acid affects the equilibrium between hydrogen peroxide/ butanedione and 3-hydroperoxy-3-hydroxybutan-2-one through reducing the effective nucleophilicity of H 2 O 2 ; and (iii) destabilizing a putative Mn(II)/PCA complex.…”
Section: ■ Results and Discussionmentioning
confidence: 87%
“…The catalyzed cis-dihydroxylation of electron-deficient alkenes such as diethylfumarate and succinimide was a major challenge in oxidation chemistry until recently, when we demonstrated that clean conversion and excellent selectivity for the cis-diol product could be achieved using acetone as solvent. 29 Under the present conditions using acetonitrile and butanedione optimized for cyclooctene epoxidation, good conversion (74%) and full selectivity was observed for the cis-dihydroxylation of diethylfumarate (Scheme 8 and Supporting Information Table S2). …”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To explore the scope of our protocol for the selective oxidation of sulfides to sulfoxides, various functionalized sulfides were employed under the optimized conditions using the SiO 2 [10][11][12][13][14][15][16][17][18]. In most cases, aryl-alkyl, aryl-aryl, alkyl-alkyl sulfides were successfully oxidized to the corresponding sulfoxides in excellent yield and high selectivity.…”
Section: Resultsmentioning
confidence: 99%
“…Among various oxidants employed in the reactions, [4][5][6][7][8][9][10][11][12][13][14] hydrogen peroxide is an attractive and environmentally-friendly oxidant owing to its low cost, high availability and cleanliness. [15][16][17][18][19] However, hydrogen peroxide alone exhibits a weak oxidative ability and a catalytic activation is required to access its full potential.…”
Section: Introductionmentioning
confidence: 99%